2014
DOI: 10.1007/s10943-014-9942-z
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Collaboration from the Islamic Perspective: The View Points for Health Providers

Abstract: Collaboration involves direct and open communication and respect for different perspectives. In particular, religious literature has many references to collaboration. This study is a report of knowledge synthesis based on qualitative systematic review by content analysis. The study surveys the concept of collaboration from the Islamic point of view and intends to answer the question, 'Does the Quran deal with the use of collaboration in human activities?' This study was conducted using electronic documents fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…In this study, the health-care team believed that the team must cooperate through teamwork in investigating the needs of patients, and the interprofessional collaboration should be considered in the care policy. [ 29 ] The results are consistent with those of other studies. It is suggested that for achieving this goal, the culture of teamwork and patient referral system to the relevant expert should be considered.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the health-care team believed that the team must cooperate through teamwork in investigating the needs of patients, and the interprofessional collaboration should be considered in the care policy. [ 29 ] The results are consistent with those of other studies. It is suggested that for achieving this goal, the culture of teamwork and patient referral system to the relevant expert should be considered.…”
Section: Discussionsupporting
confidence: 93%
“…Many hospitals in Isfahan, Iran, where this study was conducted, are served by a Religious counselor named Nasim Mehr, who helps patients faced with the challenges posed (Nasim Mehr Cultural & Consultative Office, 2008). Interprofessional collaboration between the heath care team and Religious counselor is necessary to achieve the expected outcomes in spiritual care (Edwards, Pang, Shiu & Chan, 2010;Irajpour, Ghaljaei, & Alavi, 2015;.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual distress can be identified by questions relating to how illness affects notions of life's meaning (Davison, 2010). Of course, the various spiritual needs depend on cultural, historical, and social backgrounds and their special religious values (Edwards, Pang, Shiu, & Chan, 2010), and meeting the needs of patients may be possible through interprofessional collaborations of the health care team (Irajpour, Ghaljaei, & Alavi, 2015). The researchers are aware of several studies that have been done on the spiritual needs of patients (Büssing & Koenig, 2010;Nixon & Narayanasamy, 2010;Hodge & Horvath, 2011); in Iran, most of these studies have been conducted on cancer patients (Hatamipour, Rassouli, Yaghmaie, Zendedel, & Majd, 2015;Rahnama, Khoshknab, Maddah, & Ahmadi, 2012), and, despite high mortality rates, surprisingly little research has been done to study other chronic disease patients' preferences in end-of-life and disability care.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Evidence suggests that health care professionals' willingness to explore patients' spiritual needs during advanced illness is low, 12 and this may stem from a lack of spiritual care knowledge and training. 13 Ignorance about Muslim culture in this regard has negative implications for shared decision making, 14 psychosocial support, 15 and management of disease. 16 One pilot intervention involving a one-hour educational intervention delivered by a Muslin chaplain demonstrated improved knowledge of Islamic teachings regarding end-of-life care among participating palliative care clinicians.…”
Section: Discrimination In Health Care Settingsmentioning
confidence: 99%